Search for FCNC single top-quark production at root s=7 TeV with the ATLAS detector - Onofre, A. (2012)
A search for the production of single top-quarks via flavour-changing neutral-currents is presented. Data collected with the ATLAS detector at a centre-of-mass energy of View the MathML sources=7 TeV, corresponding to an integrated luminosity of 2.05 fb−1, are used. Candidate events with a semileptonic top-quark decay signature are classified as signal- or background-like events by using several kinematic variables as input to a neural network. No signal is observed in the neural network output distribution and a Bayesian upper limit is placed on the production cross-section. The observed upper limit at 95% confidence level on the cross-section multiplied by the t→Wbt→Wb branching fraction is measured to be σqg→t×B(t→Wb)<3.9 pbσqg→t×B(t→Wb)<3.9 pb. This upper limit is converted using a model-independent approach into upper limits on the coupling strengths κugt/Λ<6.9⋅10−3 TeV−1κugt/Λ<6.9⋅10−3 TeV−1 and κcgt/Λ<1.6⋅10−2 TeV−1κcgt/Λ<1.6⋅10−2 TeV−1, where Λ is the new physics scale, and on the branching fractions B(t→ug)<5.7⋅10−5B(t→ug)<5.7⋅10−5 and B(t→cg)<2.7⋅10−4B(t→cg)<2.7⋅10−4.